The De-Totalization of History in Tim O'Brien's The Things They Carried - Fernandes, Giséle Manganelli [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2010)
This paper aims at discussing how Tim O’Brien, a veteran of the Vietnam War, reviews the American involvement in the conflict in his novel The Things They Carried (1990). The author shows the perspective of the soldiers in the stories and, therefore, presents other possibilities to analyze that historical fact. The interplay of fiction and truth is essential for O’Brien to reach the objective of reevaluating official history in order to make the readers rethink the past.
Keywords: Tim O’Brien; Vietnam War; truth; fiction; Postmodernism